MENENTUKAN RESPON ADAPTASI TERHADAP KUANTITAS DAN KOMPONEN LEUKOSIT MENCIT (MUS MUSCULUS L) PASCA RADIASI GAMMA Co-60 - Widyasari, Ni Luh; Sutapa, I Gusti Ngurah; Balik Sudarsana, I Wayan (BULETIN FISIKA, 2014)
Research has been conducted to study adaptive response of the quantity and components leucocyte after Co-60 gamma radiation. This research used 20 male mice with an average weight of 20-30 g and aged 35-95 days. The male mice given adaptive dose 0,1 Gy followed by a continuous dose of 1 Gy, 2 Gy and 3 Gy. Co-60 gamma radiation shows that the quantity of leucocytes decreased until the 30th day is called lowest point. With 0,1 Gy adaptive dose shown to reduce leucocyte damage by 13,95% compared with no adaptation dose. After passing through the lowest point, the quantity of leucocytes increased until the 60th day. With an increase in the adaptive dose is faster to reach an increase of 25,16%. On leucocyte component, which has increased similar with quantity leucocytes is the neutrophil segment and lymphocytes.